2018
DOI: 10.14715/cmb/2018.64.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Veronica persica Poir. extract – antibacterial, antifungal and scolicidal activities, and inhibitory potential on acetylcholinesterase, tyrosinase, lipoxygenase and xanthine oxidase

Abstract: Veronica persica (Persian speedwell) is a flowering plant local to Eurasia. In this study, several analyses were done to discover the antimicrobial and scolicidal activities and acetyl cholinesterase (AChE), tyrosinase (TYR), lipoxygenase (LOX), and xanthine oxidase (XO) inhibitory activities of V. persica extract.The results presented that B. subtilis was the most susceptible to the extract (MIC = 40.3 μg/mL), while P. aeruginosa was the most resistant strain (MIC = 250.9 μg/mL) among all bacteria evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Medicinal plants represent a significant source of therapeutic remedies, being also the basis of traditional or indigenous healing systems, still widely used by the majority of populations in many countries [ 1 , 2 ]. Recently, the ethnopharmacological potentials of these plant matrices have received important consideration by both scientists and the pharmaceutical industry towards complementing or even replacing conventional pharmacotherapies [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants represent a significant source of therapeutic remedies, being also the basis of traditional or indigenous healing systems, still widely used by the majority of populations in many countries [ 1 , 2 ]. Recently, the ethnopharmacological potentials of these plant matrices have received important consideration by both scientists and the pharmaceutical industry towards complementing or even replacing conventional pharmacotherapies [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants are known as great source of natural curative agents with huge therapeutic potential (Sharifi-Rad et al, 2018;Sharifi-Rad et al, 2018a). Use of medicinal herbs to cure a variety of human and animal diseases, have suggested their effectiveness in different medical areas (Sharifi-Rad et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Mocan et al reported on the presence of antimicrobial active compounds in three Veronica species, i.e., Veronica orchidea, teucrium, and officinalis [53]. Javad Sharifi-Rad et al [54] reported antifungal and antibacterial agents in Veronica persica poir species. Stojkvoic et al [55] reported potent antibacterial agent in the extract of Veronica montana species.…”
Section: Resultsmentioning
confidence: 99%